PTU-006 The sequential organ failure assessment (SOFA) score is an effective triage marker following staggered paracetamol (acetaminophen) overdose. (28th May 2012) - Craig, D G; Zafar, S; Reid, T; Davidson, J; Martin, K; Hayes, P C; Simpson, K J
Abstract : Introduction: The Sequential Organ Failure Assessment (SOFA) score is an effective triage marker following single time point paracetamol (acetaminophen) overdose, 1 but has not been evaluated following staggered paracetamol overdose. The aims of this study were to evaluate the prognostic accuracy of the SOFA score in a cohort of severe acute liver injury patients following staggered paracetamol overdose. Methods: Time-course analysis of 50 staggered paracetamol overdoses admitted to a tertiary liver centre. Individual laboratory samples were correlated with the corresponding clinical parameters in relation to time from admission, and the daily SOFA score calculated. Results: A total of 39/50 (78%) patients developed hepatic encephalopathy, and therefore acute liver failure. The area under the SOFA receiver operator characteristic for death/liver transplantation was 87.4 (95% CI 73.2 to 95.7), 94.3 (95% CI 82.5 to 99.1), and 98.4 (95% CI 84.3 to 100.0) at 0, 24, and 48 h respectively post-admission. A SOFA score of <6 at tertiary care admission predicted survival with a sensitivity of 100.0% (95% CI 76.8% to 100.0%) and specificity of 58.3% (95% CI 40.8% to 74.5%), compared with 85.7% (95% CI 60.6% to 97.4%) and 75.0% (95% CI 65.2% to 79.5%) respectively for the modified Kings College criteria. Only 2/21 patients with an admission SOFA score <6 required renal replacement therapy or intracerebral pressure monitoring. SOFA significantly outperformed the Model for End-stage Liver Disease at 0 (p=0.0013), 24 (p=0.0001) and 48 h (p=0.0193) following admission. Conclusion: A SOFA score <6 at tertiary care admission following a staggered paracetamol overdose carries a high negative predictive value. The SOFA score could improve triage of high risk staggered paracetamol overdose patients. Competing interests: None declared. Reference: 1. Craig DG, Reid TW, Martin KG, et al . The systemic inflammatory response syndrome and sequential organ failure assessment scores are effective triage markers following paracetamol (acetaminophen) overdose. Aliment Pharmacol Ther 2011;34 :219–28.